Searching for bequest motives and attitudes to leaving a bequest among Malaysian Muslims - Suhaili Alma'amun, (Penerbit Universiti Kebangsaan Malaysia, 2012)
This study aims to identify bequest motives and investigate the attitudes to leaving a bequest among malaysian Muslims.Data are collected by means of questionnaire and analysed with multinomial logit model.Results from this model are compared with the verbatim responses given by respondents. Evidences suggest to co-existences of various bequest motives with no preference in order, namely pure life-cycle,life-cycle with some strategic or exchange features.altruistic and dynastic bequest models. However, the domination of one particular bequest motive over others is solved via analaysis carried out on the verbatim responses.